Systems and Political Development in Malaysia - O. Argo Victoria; Fadly Ameer (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
Malaysia is a country in Southeast Asia with an area of 329 758 km2 and a population in 2007 amounted to 27.17 million. Of the total population in 2007, 60% are ethnic Malay “Bumiputera”, 26% ethnic Chinese, 8% Indians, 5% other ethnic Bumiputera, and 1% other ethnic groups such as Arabic, Sinhalese, Eurasian and Europe.[1] Under the constitution, Malays are Malaysian citizens who practice a traditional Malay, Melayu Language, and Muslim. Approximately 25% of the Malaysian population is Chinese, and 7% is made up of India. Almost 85% of the races Indians in Malaysia are Tamil community. More than half the population of Sarawak and Sabah 66% of the population consists of non-Malay indigenous people. The entry of another race to some extent reduce the percentage of indigenous population in the two states. In addition, Malaysia also has a population that comes out of Europe and the Middle East. Malaysia's population density is not distributed evenly, with 17 million of the 25 million people living in Peninsula Malaysia.Keywords: Malaysia; Politic; Constitutional.[1] Barbara Watson Andaya and Leonard Andaya, 1983, History of Malaysia, Petaling Jaya: Macmillan Publishers, p. 6-7